Expression of the character of nationality in phraseological units - Khaydarova , Guzalkhon Khamdamjon kizi (The Lingua Spectrum, 2026)
This article explores the linguocultural nature of phraseological units and their role in reflecting the interconnection between language, culture, and national mentality. The study examines the semantic, structural, and functional features of phraseological units, emphasizing their stability and idiomatic character within the language system. A comparative analysis of Uzbek and English phraseological units is conducted to identify both similarities and differences in their usage and meaning. Phraseological units are interpreted as cultural “codes” that encapsulate a nation’s historical experience, traditions, moral values, and social norms. Special attention is given to imagery as a defining feature of phraseology, highlighting its origin in national ways of thinking and perception. The article also addresses key challenges in translating phraseological units, particularly the limitations of literal translation and the importance of preserving cultural relevance. The findings demonstrate that phraseological units not only enrich expressive speech but also serve as essential tools for effective intercultural communication. This research contributes to a deeper understanding of how language encodes cultural identity and provides insights valuable for linguists, translators, and scholars interested in cross-cultural studies.